The Influence Of Problem-Based Learning On Student's Critical Thiniking Skills In Chemical Equilibrium - Fatih Enzati Sayoga Wardana; Nurfina Aznam (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the influence of the PBL learning model on students' critical thinking skills, as well as to analyze changes in students' critical thinking skills before and after the implementation of PBL on reaction equilibrium material. The research method used was a quasi-experiment with a pretest-posttest control group design. The research sample consisted of an experimental class and a control class with a total of 72 students. The data were analyzed using an independent sample t-test to determine the effect of PBL learning on students' critical thinking skills, while a paired sample t-test was used to determine the changes before and after the treatment. The results showed that PBL learning significantly improved students' critical thinking skills. In addition, there was an increase in critical thinking skills in students before and after participating in PBL learning. Thus, the application of PBL learning significantly influenced and improved the critical thinking skills of high school students on the subject of chemical equilibrium.